MENINGKATKAN KETERAMPILAN MEMBUAT BROS MANIK-MANIK AKLIRIK MELALUI METODE ANALISIS TUGAS BAGI ANAK TUNAGRAHITA RINGAN - Nilam Syahrina, Yosfan Azwandi, Elsa Efrina (Universitas Negeri Padang, 2013)
The research was The background by the problem of mild mental retardation children of class VII / C, who has the ability to make brooches still less, and still be in making acrylic beads brooch. The purpose of this study is that children can make acrylic beads brooch with six steps that have been given. Research hypothesis reads: task analysis method to improve the skills of making acrylic beaded brooch for mild mental retardation children in special schools x Pearl Budi Lubuk Alung.This research Single Subject Research approach, the A B design. Subjects were one child mild mental retardation. The target behavior is to increase the skills brooch acrylic beads. This research was first seen from the baseline condition (A child's ability to make skills brooch acrylic beads), and then continued in the intervention condition (skills make brooches with acrylic beads task analysis method). Data processed by the graph, so the results of this study can be illustrated clearly. These results indicate that the method can improve the skills of task analysis to make acrylic beads brooch. It is from the baseline condition x students are only able to obtain scores: 3, 3, 4, 3, 4, 4 in the intervention condition, students get a score that is x: 4, 6, 6, 6, 6, 8, 9, 9 , 11, 12, 12.